Relationship of Eggshell Thickness to Thermal Gradients Across the Shell at the Large and Equatorial Regions of Ross 708 Broiler Hatching Egg - Durojaye, O.A.; To, S.D.F.; Elliott, K.E.C.; Gerard, P.D.; Peebles , E.D. (International Journal of Poultry Science, 2019)
Background and Objective: This study was designed to examine the relationship between the thickness and thermal barrier property of the eggshell of embryonated Ross 708 broiler hatching eggs. Methodology: On each of 8 levels of a single-stage incubator, 43 eggs were weighed and set. Transponders were implanted in the air cell of 10 eggs per level at 12 d of incubation (DOI) and shell thickness at the large end (LSTH) of those eggs was measured at 19 DOI. Along with air cell temperature (ACT), external surface temperature of the shell was measured daily at the equator (EST) and large end (LST) of the egg by infrared thermometry at 10 AM and 4 PM between 12 and 19 DOI. Thermal gradients across the shell at the equator and large end of the egg were expressed as differences between ACT and EST (TE) and ACT and LST (TL). Results: There was a significant (p<0.0001) location in the egg ×time period interaction for the temperature readings and thermal gradients across the eggshell. At 4 PM on 12 DOI, 10 AM on 13 and 14 DOI and 10 AM and 4 PM on 15-19 DOI, ACT was higher than EST and EST was higher than LST. However, at 4 PM on 13 and 14 DOI, ACT and EST were not significantly different but both were higher than LST. At all time periods examined, TE was lower than TL. Mean EST and LST were positively correlated (p<0.0001). However, significant negative correlations were observed between LSTH and TE at 10 AM on 17 DOI and between LSTH and TL at 10AM and 4 PM on 16 and 17 DOI and at 10 AM on 18 DOI. Conclusion: Although, EST and LST are positively correlated, EST is more closely related to ACT than is LST and an increase in LSTH, within the range observed in this study, does not increase the shell’s function as a thermal barrier in embryonated Ross 708 broiler hatching eggs.